2022
DOI: 10.3390/microorganisms10122506
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia Epidemiology, Resistance Characteristics, and Clinical Outcomes: Understanding of the Recent Three Years’ Trends

Abstract: Background. Stenotrophomonas maltophilia is an emerging pathogen classified as a public health concern, that infects critically ill patients and has expressed resistance against antimicrobial therapy. The aim of this study was to examine the epidemiological pattern, resistance characteristics and clinical outcomes of S. maltophilia infections in hospitalized patients. Methods. The study included 393 S. maltophilia isolates from different clinical specimens as well as the clinical data of 209 Intensive Care Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…In recent years, S. maltophilia has been relatively stable in third place among non‐fermenting Gram‐negative bacteria, after P. aeruginosa and A. baumannii , according to the CHINET monitoring service 15 . Patients with severely impaired or weakened immune functions were more susceptible to serious consequences when infected with S. maltophilia , suggesting that the respiratory tract was the main site of colonization and infection of S. maltophilia , which may have been associated with its ability to form biofilms and colonize the respiratory tract of hospitalized patients 16 . Recently, S. maltophilia was reported as one of the secondary bacterial infections in ICU patients with COVID‐19, 12 which is similar to what was found in this study: the infection rate of S. maltophilia was higher in the COVID‐19 group than in the CNT group.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, S. maltophilia has been relatively stable in third place among non‐fermenting Gram‐negative bacteria, after P. aeruginosa and A. baumannii , according to the CHINET monitoring service 15 . Patients with severely impaired or weakened immune functions were more susceptible to serious consequences when infected with S. maltophilia , suggesting that the respiratory tract was the main site of colonization and infection of S. maltophilia , which may have been associated with its ability to form biofilms and colonize the respiratory tract of hospitalized patients 16 . Recently, S. maltophilia was reported as one of the secondary bacterial infections in ICU patients with COVID‐19, 12 which is similar to what was found in this study: the infection rate of S. maltophilia was higher in the COVID‐19 group than in the CNT group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severely impaired or weakened immune functions were more susceptible to serious consequences when infected with S. maltophilia, suggesting that the respiratory tract was the main site of colonization and infection ofS. maltophilia , which may have been associated with its ability to form biofilms and colonize the respiratory tract of hospitalized patients [13] . Recently, S. maltophilia was reported as one of the secondary bacterial infections in ICU patients with COVID-19 [9] , which is similar to what was found in this study: the infection rate of S. maltophilia was higher in the COVID-19 group than in the CNT group.…”
Section: Discussionmentioning
confidence: 99%
“…Even though commonly isolated due to secondary bacteremia, primary bacteremia is not uncommonly reported, recorded in 45% of patients in a recent study [ 7 , 8 , 9 ]. The increasing incidence of S. maltophilia infections has been highlighted during the COVID-19 epidemic [ 10 ]. Recent studies have shown increased prevalence of S. maltophilia infections, among hospitalized COVID-19 patients, leading the race of pathogens together with A.baumani [ 11 ].…”
Section: Introductionmentioning
confidence: 99%